Speaking Teaching Strategies Used by Vocational School EFL Teacher - Hasibuan, Ikhsan Ramadhan; Panjaitan, Andre Bona Josua; Saragih, Erikson (English Language in Focus (ELIF), 2022)
This study aims to represent vocational school teachers' strategies for teaching speaking to students at secondary level in Medan, North Sumatra province, Indonesia. This research is a qualitative descriptive research design with 13 participants taking part. In collecting the data, the researcher used a structured self-administered questionnaire with ten questions divided into three parts: introductory, practice, and evaluation. The questions in the introductory section were all about the teacher's preparation process for teaching speaking, such as what resources they used and whether the reference sources were relevant to the syllabus. The practice session questions then go through the teaching and learning process, including what methods teachers use, why they choose this method, what activities teachers do, and what activities the students do during the learning speaking skills process. Lastly, the evaluation session questions include activities that occur after the teaching and learning process, such as how the teacher assesses students, what assessment criteria or rubrics are commonly used, and what suggestions are supposed to help students in their speaking skill problems.